Monetary Incentives Versus Fringe Benefits: The Motivation Behind Generation X and Millennial Employees - Princes Diane R Escosura (RSF Press, 2023)
This study focused on the lived experience of employees in the Department of Science and Technology–Forest Product Research and Development Institute as to the motivation from monetary incentives or fringe benefits. The research design used was qualitative, with phenomenology as an approach. The study explored the experiences and motivation of Generation X and millennial employees in the Department of Science and Technology–Forest Product Research and Development Institute. Based on the results, employees reflected on their overall experiences that they manifest on non-monetary benefits or fringe benefits rather than monetary incentives they received. The employees were acquainted with the experience that arose from the testimony, which showed that motivated employees were more likely to be productive, happier in their jobs, and remained with their company for a longer amount of time by creating a great work atmosphere. Giving employees chances to learn and develop, enough incentives and benefits for excellent performance resulted in their satisfaction with their work. The researcher considered the employees experiencing job satisfaction and dissatisfaction based on Frederick Herzberg's theory, also known as the Two Factor Theory that developed to better understand an employee's attitude and drive toward the job. As an output, the researcher suggested establishing a committee of employees at the Department of Science and Technology – Forest Products Research and Development Institute named 4C's or Cope Capacity Counseling Committee, which aimed to promote financial, emotional, physical, social, and psychological concerns of the employee's motivation at their workplace.